Diabetes Resilience Training on Self-Care, Glycemic Control, and Diabetes Burnout of Adult Type 2 Diabetes Mellitus - Hidayat Arifin; Kusnanto Kusnanto; Erna Dwi Wahyuni; Rifky Octavia Pradipta (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2019)
Introduction: Treatment that must continue, control, and diet that must be obeyed by people with DM can cause boredom (burnout) - inability to care for themselves, and blood sugar that is not controlled. The purpose of this study was to determine the effect of diabetes resilience training on self-care, glycemic control, and diabetes burnout of adult type 2 diabetes mellitus. Methods: This study was a quasi-experimental design. The total samples were 70 respondents (treatment and control) obtained by cluster sampling. The independent variable was diabetes resilience training and dependent variables were self-care, glycemic control, and diabetes burnout. The intervention provided for one month with four meetings. Instrument used self-care questionnaire of Self-Care Inventory-Revised (SCI-R), glycemic control questionnaire used an observation sheet for fasting blood sugar, and diabetes burnout questionnaire used Diabetes Distress-Screening Scale (DDS17). Data were analyzed with Wilcoxon signed ranks test, Mann Whitney U Test, Independent-sample t-test, and 1-Sample K-S. Results: There was an effect of diabetes resilience training on self-care (p = 0.003; p <0.05), glycemic control (p = 0.020; p <0.05), and diabetes burnout (p = 0,000; p <0.05). Conclusions: Diabetes resilience training provided by researchers to respondents can improve good self-care behavior, decreased glycemic control values, and decreased distress (diabetes burnout) in adult type 2 diabetes mellitus.  Based on the results, it is recomandation to nurses and health care provider to implementation the diabetes resilience training regularly.